Inference on constant stress accelerated life tests for log-location-scale lifetime distributions with type-I hybrid censoring. Issue 4 (4th March 2019) - Lin, Chien-Tai; Hsu, Yao-Yu; Lee, Siao-Yu; Balakrishnan, N.
ABSTRACT: In this paper, we consider a constant stress accelerated life test terminated by a hybrid Type-I censoring at the first stress level. The model is based on a general log-location-scale lifetime distribution with mean life being a linear function of stress and with constant scale. We obtain the maximum likelihood estimators (MLE) and the approximate maximum likelihood estimators (AMLE) of the model parameters. Approximate confidence intervals, likelihood ratio tests and two bootstrap methods are used to construct confidence intervals for the unknown parameters of the Weibull and lognormal distributions using the MLEs. Finally, a simulation study and two illustrative examples are provided to demonstrate the performance of the developed inferential methods.